Pemberian Kombinasi Pakan Keong Macan Dan Ikan Rucah Terhadap Pertumbuhan Dan Kelulushidupan Kepiting Bakau (Scylla paramamosain) - Asyhariyati, Anis Idha; Samidjan, Istiyanto; Rachmawati, Diana (Journal of Aquaculture Management and Technology, 2013)
In the cultivation of mangrove crab feed is a great operational capital in cultivation beyond the provision of seedlings. For that feed used must be able to act as efficient as possible, so that it can push the cost minimal feed without reducing the level of maximum production. This research aims to know the combination effect of feed the babylon snail and trash fish to theg growth and survival mangrove crab (Scylla paramamosain). This research was carried out in April until Juni 2012 at the farming village of Tugurejo, Mangkang, Semarang District. Animal test used is the mangrove crab with average initial weight of 100 grams. Feed The babylon snail and trash fish. experimental method uses that take place in the field with a randomized Complete Design (RAL), namely 3 and 3 treatment of Deuteronomy. The treatment A (feed The babylon snail), B (trash fish), C (feed combination The babylon snail and trash fish). The variables measured growth (SGR), the utilization of the feed (EPP, PER) and SR, as well as water quality. The results showed a combination feed the babylon snail and fish test rucah fresh gives but has no effect the real influence (P<0,05) against SGR, PER, EPP and SR mangrove crab.